The Transformation of Science Communication in VUCA Era: Study of Media Startups Kok Bisa in Indonesia - Syora Alya Eka Putri; Ricardi S Adnan (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2021)
This study analyzes the transformation of science communication conducted by media startups in the VUCA era in Indonesia. In the information age, especially during the COVID-19 pandemic, people are increasingly dependent on educational needs. Nevertheless, there are challenges of information explosion that are too dynamic and less effective. As a result, media startups have implemented science communication innovations to open public access to science. Previous studies have acknowledged science communication models using visual literacy approaches and using narrative explanations. Therefore, the model faces significant challenges such as information uncertainty, establishing a science communication ecosystem, and ambiguity due to cultural change. Employing qualitative content analysis methods, this article found that media startups face the biggest challenges in developing science communication. On the other hand, the VUCA era can be a driving tool for media startups to conduct adaptive social transformation in the field of science communication.